1997
DOI: 10.1177/00220345970760100901
|View full text |Cite
|
Sign up to set email alerts
|

A Within-subject Comparison of Mandibular Long-bar and Hybrid Implant-supported Prostheses: Psychometric Evaluation and Patient Preference

Abstract: Although it has been shown that patients are more satisfied with prostheses supported by implants than with conventional dentures, there have been few direct comparisons of the various designs of implant-supported prostheses. This within-subject crossover clinical trial was designed to compare two forms of removable prostheses which are frequently prescribed for the edentulous mandible: a long-bar overdenture supported by 4 implants and a two-implant hybrid overdenture. Sixteen completely edentulous subjects w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
80
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(86 citation statements)
references
References 18 publications
3
80
1
Order By: Relevance
“…12 Their use in prosthodontics is also justified, since it has been shown that patient satisfaction instruments are sensitive enough to capture clinically significant differences between various prosthodontic treatments. 8,13 One of the advantages of using patient satisfaction as a treatment outcome is its simplicity and comprehensibility for clinical practitioners. However, some disadvantages have been associated with these measures.…”
Section: Introductionmentioning
confidence: 99%
“…12 Their use in prosthodontics is also justified, since it has been shown that patient satisfaction instruments are sensitive enough to capture clinically significant differences between various prosthodontic treatments. 8,13 One of the advantages of using patient satisfaction as a treatment outcome is its simplicity and comprehensibility for clinical practitioners. However, some disadvantages have been associated with these measures.…”
Section: Introductionmentioning
confidence: 99%
“…Further, related outcomes could not be extracted from nine articles [11][12][13][14][15][16][17][18][19] , one article compared different implant systems and opposing dentition was not reported 20 . In one article 21 27 corresponding to (Visser et al 35 ), Batenburg et al 28 , and de Jong et al…”
Section: Results:-mentioning
confidence: 99%
“…The increased prosthesis rigidity creates a stable occlusal plane, reduces loading of denture-bearing areas [31], and decreases posterior mandibular ridge resorption [28]. Moreover, it improves chewing [32], decreases the incidence of prosthodontic maintenance [33], reduces soft tissue irritation, protects mental nerve, and diminishes problems of high muscle attachment and prominent mylohyoid ridge [20]. The supporting area of bars with distal cantilevers also was found to be greater than straight or slightly bent bars without distal cantilevers [19].…”
Section: Introductionmentioning
confidence: 99%